Disposal of animal healthcare services waste in southern Brazil: One Health at risk - Kelly Scherer de Oliveira; Larissa Morello; Simone Vassem de Oliveira; Lenita Agostinetto; Bruna Fernanda da Silva; Ana Emilia Siegloch (Centro Brasileiro de Estudos de Saúde, 2020)
ABSTRACT Brazilian animal livestock is in full expansion but linked to the use of veterinary drugs which may be considered as emerging contaminants. The study aimed to characterize the disposal of Animal Healthcare Service Waste (AHSW), especially of veterinary drugs, besides identifying the most used drugs in the city of São Joaquim municipality, southern Brazil. Eighty-four cattle ranchers were interviewed through a structured questionnaire with closed questions about drugs use and disposal of the AHSW. The active ingredients of drugs most used were the antiparasitic ivermectin (68% of properties) and the antimicrobial oxytetracycline (48%). After the use, the disposal of the AHSW, including expired drugs, leftovers and wrapper, was the disposal next to the domestic trash, burned and deposited in the soil. The Chi square test showed association between the age of the participants and the disposal of sharp objects (X2 = 36,36, p= 0,020), showing that farmers aged above 60 years usually reuse, the ones who are 20 years old return to the place where they acquired the material and the rest adopts improper practices. The disposal practices of the AHSW adopted in the properties are still in disagreement with the current Brazilian legislation and may cause adverse effects on human, animal and environmental health.